comparative performance — direct seeded rice vs transplanted rice - Gangwar, K S; Tomar, O K (Indian Farming, 2015)
Direct dry seeded rice is the future of the farmers of the country as the rice is the principal crop of the Indian people on one hand and water availability for growing the rice on the other. Direct seeded rice was found more productive, profitable and water saver as compared to transplanted rice as it matures 10 days earlier and provides sufficient time for next crop to be established in the field.